STUDY THE EFFECT OF ISOLATED ALKALOID FROM HALOXYLON SALICORNICUM PLANT ON SOME HEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN GASTRIC ULCERATION RABBITS INDUCED BY INDOMETHACIN - Noor Abdul Amir Jabbar; Arwa H.M. AL-Saeed; Batool Saleh Haddad (Basrah Journal of Veterinary Research)
This study was undertaken to isolate alkaloids from Haloxylon Salicornicum plant to show the curative effect after short-term daily orall administration for 10 days (300 mg/Kg B.W.) on gastric ulcer,hematological parameters and some biochemical parameters in gastric ulceration rabbits induced by indomethacin.Moreover,some qualitative chemical analysis,thin layer chromatography,UVspectroscopy and FTIR spectroscopy were used to identify alkaloid compound .Rabbits were divided randomly into three groups,6 rabbits in each.Group one received 3 ml normal saline orally (control group).Group two was treated with indomethacin (75 mg/Kg B.W.) (gastric ulceration group).Third group gastric ulceration rabbits post-treated with isolated alkaloid (300 mg/Kg B.W.).The results of the present study indicated that isolated alkaloid has Rf= 0.86,high significant decreased (p≤0.001) in RBC,Hb,PCVand mucin,(P ≤ 0.01) in MCHC and PH,no significant difference (P ≥ 0.05) in MCH in gastric ulceration rabbits compared with control group and observed high significant increased (p≤0.001) in MCV, MDA and gastric juce volume,WBCcount appeared high significant increased (P≤0.01).While, observed high significant increased(P≤ 0.001) in Hb,PCVand mucin,(P≤ 0.01) in RBC,MCHC and pH.Significant increased(P≤0.05) in MCH after treated with isolated alkaloid and high significantly decrease (P ≤ 0.001)in MCV,gastric juce volume and MDA   and significant decrease (p≤0.05) inWBC count compared with gastric ulceration group .This study concluded that isolated alkaloid from Haloxylon Salicoricum plant can be used to treat gastric ulcer effectively .